TIKTOK SOCIAL MEDIA USAGE MOTIVES: USES AND GRATIFICATION THEORY ANALYSIS - Herna (Universitas prof. Dr. Moestopo (Beragama), 2022)
The purpose of the study was to find out the motives for using TikTok social media to get gratification. Users choose a medium to meet the needs and get satisfaction. This study describes the usefulness and satisfaction of using TikTok social media using the Uses and Gratification Theory. The study used a qualitative approach with data collection methods with in-depth interviews directly with five informants. The results of the study explain that the first motive for using TikTok media is to get entertainment. The Tiktok application is in fact trending and is seen by users as a new application which is not only interesting to use, but also used by many others, thus motivating users to use TikTok as well. The second motivation is to get information. Users get a lot of information such as health information, beauty tutorials, makeup, clothing, and even culinary references. The third motive The next motive is to present themselves or self-expression through videos that they make creatively which is added with information. The peak satisfaction with the self-presentation motive is feedback from others regarding the content presented. The fourth motivation is the motive to escape from boredom that can lead to addiction to TikTok media.